2021
DOI: 10.3389/fimmu.2021.738760
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of circRNA and mRNA Profiles in Vogt–Koyanagi–Harada Disease

Abstract: Recent studies revealed that circular RNAs (circRNAs) are important in numerous biological process and involved in autoimmune diseases. However, their role in Vogt–Koyanagi–Harada (VKH) disease, a classical autoimmune disease, is not yet known. This research aimed to study the expression profile of mRNAs, microRNAs (miRNAs) and circRNAs and investigate the influence of circRNAs on the pathogenesis of VKH disease. We identified circRNAs, miRNAs, and mRNAs expression profiles in CD4+ T cells between 4 VKH patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Recently, numerous studies have shown that the ceRNA networks regulation, that is the interaction among circRNAs, miRNAs, and mRNAs, was identified to widely exist in various diseases in different species (64)(65)(66). To investigate the ceRNA network and the functions of circRNAs against APEC infection in chicken macrophages, a putative circRNA-miRNA-mRNA network was constructed in current study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous studies have shown that the ceRNA networks regulation, that is the interaction among circRNAs, miRNAs, and mRNAs, was identified to widely exist in various diseases in different species (64)(65)(66). To investigate the ceRNA network and the functions of circRNAs against APEC infection in chicken macrophages, a putative circRNA-miRNA-mRNA network was constructed in current study.…”
Section: Discussionmentioning
confidence: 99%
“…Another research purified the CD4+ T cells from PBMCs and extracted total RNA of CD4+ T cells. RNA-seq was conducted, revealing that circular RNAs (cicRNAs) may have an important immunomodulatory function in the development of VKH disease ( 25 ). As the existing researches have revealed the crucial role of immune cells and molecules in the development of VKH disease, our research group innovatively intersected the screened DEGs between VKH patients and healthy controls with the immune dataset and finally found out six immune hub genes in VKH disease, furtherly providing a new insight into the pathogenesis and treatment of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are small noncoding RNAs that regulate gene expression at the post-transcriptional level [13]. Several investigators have reported on the feasibility of using miRNAs as biomarkers for the diagnosis of non-infectious uveitis, and miRNAs may also advance our understanding of the pathogenic mechanisms involved in these diseases [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%